Electro-Catalytic Behavior of Silver Nanoparticles Embedded in Potato and Tapioca Starch for Oxygen Reduction Reaction - Kalantari, Katayoon; Afifi, Amalina Muhammad; Nia, Pooria Moozarm; Izadiyan, Zahra; Kalantari, Alireza; Abouzari-lotf, Ebrahim (Wiley-VCH Verlag, 2018)
The present work demonstrates an eco-friendly and facile method for the synthesis of tapioca and potato starches incorporated by silver nanoparticles hereafter named (T-Ag/NPs) and (P-Ag/NPs), respectively. The analysis of UV–vis showed the appearance of surface plasmon resonance. The TEM analysis shows the formation of highly distributed Ag/NPs with an average diameter and standard deviation of 19.65 ± 2.45 and 12.27 ±7.39 nm for (P-Ag/NPs) and (T-Ag/NPs), respectively. The prepared (T-Ag/NPs) show remarkable potential applicability in energy as low-cost electrode material compared with (P-Ag/NPs). They are used as a non-precious catalyst for oxygen reduction reaction (ORR) in the alkaline medium. The presence of starch promotes long-term stability up to 1000 cycles and avoid the dissolution and agglomeration of silver nanoparticles. The (T-Ag/NPs) show significant stability and reproducibility.